Final fight : when the trauma of war comes home [videorecording (DVD)] ([Cal Turner Family Foundation], 2023)
The suicide epidemic of our veterans is much worse than is commonly known. Suicide numbers from combat veterans and survivors of Military Sexual Trauma are 4.5x higher than the total number of service members tragically lost in battle during the entire Global War on Terror. Final Fight profiles a diverse set of veterans and their responses to living with combat trauma and military sexual trauma. We interview leading experts in the field of PTS and brain science within the scope of veterans mental health-seeking to find ways for our veterans to coexist with their traumas and lead the lives they so wholeheartedly deserve. Many of the veterans we interviewed are more comfortable on the front lines of battle than feeling the pressures of a "normal" life-making coming home the Final Fight.